Our Peers—Empowerment and Navigational Support (OP-ENS): Development of a Peer Health Navigator Intervention to Support Medicaid Beneficiaries With Physical Disabilities. (April 2019) - Magasi, Susan; Papadimitriou, Christina; Panko Reis, Judy; The, Kimberly; Thomas, Jennifer; VanPuymbrouck, Laura; Wilson, Tom
People with disabilities (PWD) are a health disparities population who experience well-documented physical, structural, attitudinal, and financial barriers to health care. The disability rights community is deeply engaged in advocacy to promote health care justice for all PWD. As the community continues to work toward systems change, there is a critical need for community-directed interventions that ensure individuals with disabilities are able to access the health care services they need and are entitled to. Peer health navigator (PHN) programs have been shown to help people from diverse underserved communities break down barriers to health care. The PHN model has not been systematically adapted to meet the needs of PWD. In this article, we describe the collaborative process of developing Our Peers—Empowerment and Navigational Supports (OP-ENS), an evidence-informed PHN intervention for Medicaid beneficiaries with physical disabilities in Chicago, IL, USA. Our Peers—Empowerment and Navigational Supports is a 12-month community-based PHN intervention that pairs Medicaid beneficiaries with physical disabilities (peers) with disability PHNs who use a structured recursive process of barrier identification and asset mapping, goal setting, and action planning to help peers meet their health care needs. Our Peers—Empowerment and Navigational Supports was developed by a collaborative team that included disability rights leaders, representatives from a Medicaid managed care organization, and academic disability health care justice researchers. We highlight both the conceptual and empirical evidence that informed OP-ENS as well as the lessons learned that can assist future developers.